Development of a geographical information system based transport assessment approach in rural South Africa - The Case of Healthcare Accessibility in Cape Winelands District Municipality - Ma-Kiese, Stephane Simon Masamba (Department of Civil Engineering, 2020)
For communities in urban and rural areas, access to healthcare facilities is a very significant concern of service delivery to both public policy makers and urban planners. Many healthcare systems set one of their primary objectives to achieve equity and ease of access to healthcare facilities for the populations that they serve. Spatial distribution of population, transport infrastructure, as well as spatial distribution of healthcare facilities are key characteristics that influence the disparities in spatial accessibility to healthcare facilities. Regardless of the permanent interest in transport accessibility, it is often uncertain how different types of accessibility measures relate to one another and which conditions are best for applications. In general, the current study undertakes a statistical comparison among three spatial accessibility measures (representing the main categories of spatial accessibility models) to determine whether they are comparable and/or interchangeable. Specifically, this study aims to use a geographical information system based approach combined with spatial accessibility measures, in a case study, derived from fine spatial resolution datasets, to characterise and divulge spatial variations in individual’s access to healthcare facilities and identify deprived locations/local communities in a selected District Municipality of the Western Cape, South Africa. Results indicate that the main categories of spatial accessibility measures provide different interpretations of accessibility that cannot be reproduced by each other. However, the accessibility measures show a significant similar trend in variations of individual’s accessibility to healthcare services for the communities of Cape Winelands District Municipality. The study establishes that within the Cape Winelands there exist spatial variations in the distribution of accessibility to healthcare and characterises these variations.